2023
DOI: 10.1515/mt-2022-0244
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat input on hot cracking sensitivity of the EA395-9 filler metal

Abstract: Microcracks are always present in the deposited metal of 10MnNi2MoVA steel weld seam, which affects the safety of the power plant steam pipeline. It is important to investigate the effect of heat input on the hot cracking sensitivity of the EA395-9 weld metal. In this work, the deposition of the weld metal of EA395-9 was prepared, then the hot cracking tendency of the weld with the different heat input was analyzed and observed. The results show that the moderate welding heat input can help to avoid hot cracki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, higher heat input, pulse frequency and thermal pulse frequency imparted a negative effect on the volume fractions of AF. Yang [13] demonstrated that the moderate welding heat input can help to avoid hot cracking. In addition, Dong [14] found that increasing the welding heat input could suppress the formation of martensite (M) and reduce the microhardness of heat affected zone (HAZ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, higher heat input, pulse frequency and thermal pulse frequency imparted a negative effect on the volume fractions of AF. Yang [13] demonstrated that the moderate welding heat input can help to avoid hot cracking. In addition, Dong [14] found that increasing the welding heat input could suppress the formation of martensite (M) and reduce the microhardness of heat affected zone (HAZ).…”
Section: Introductionmentioning
confidence: 99%
“…Most research mainly focuses on the effect of the heat input and microstructure on the impact toughness of deposited metal. However, the presence of inclusion is generally thought to be a major factor that deteriorates the toughness of deposited metal [8][9][10][11][12][13][14][15][16][17][18]. Especially when the inclusion is modified by rare earth elements, because rare earth elements are sensitive to the change of welding thermal cycle temperature, the change of heat input will affect the reaction and existing state of rare earth elements and other alloy elements.…”
Section: Introductionmentioning
confidence: 99%